Measurement of Application Gap of Energy Management System According to The Standard ISO 50001:2011/ Case Study in North Oil Company - حسين, ذو الفقار جاسم; شاهين, د. نداء صالح مهدي (Journal of Petroleum Research and Studies, 2019)
The research aims at measuring the gap between the actual reality and the requirements of the energy management system according to the standard (ISO 50001: 2011) in the North Oil Company. The research starts from the problem of high consumption, unattended and uncontrolled for the four sources of energy adopted by the company (electricity, benzene, gasoline and water) And the negative effects on the external and internal environment resulting from poor energy consumption. In order to access the scientific facts, the case study, which includes observations, field cohabitation and direct encounters, was used. The checklist shown was also used. The results show significant gaps between the actual reality and the requirements of the standard (ISO 50001: 2011). The results of the evaluation showed a total gap of (0.57) for the source of electricity, and a total gap of (0.62) for the source of benzene, and the total gap for the source of gasoline was (0.65), As well the total gap of water source (0.82).